Remedial Measures to Rectify Blackspot on National Highway - Pallavi Patil; Nagesh Suryawanshi; Sushma Kulkarni (ASEAN Journal of Science and Engineering, 2021)
Road safety becomes a major concern for the regulatory authorities in India. Indian road safety situation is many times worse when compared to the developed countries of the world, leaving much to be done in the field of Road Safety Management. Road safety is defined as the absence of crashes, injuries, and fatalities. The term "safety" implies that there are no occurrences of accidents. The present study was conducted to identify the blackspot stretch on which Injury frequency and severity rate are more. Blackspot is a stretch of National Highway of about 500 m in Length in which either 5 road accidents (in all three years put together involving fatalities/ grievous injuries) took place during the last 3 calendar years or 10 fatalities (in all three years put together) took place during the last 3 calendar years. From the traffic survey, it was found that since 2015-2020 the area near MIET College is not safe for the riders. Statically Casualties occurred shows that 12 % cases related to Fatality, 38% cases related to Minor injury, and 50 % cases have been constituted for Major injury. MIET College area is located at Chainage 500+740 wherein it is located at the ‘At-Grade’ Intersection. In the present paper, the attempt is made to provide a practical Solution to rectify Blackspot. It includes providing Short-term and Long-Term Remedial Measures. Remedial measures suggested combating the fatalities with exponential scale and ensuring the safety of identified blackspots.